IMPLEMENTASI MODEL WINDOW SHOPPING DALAM PEMBELAJARAN MEMBANDINGKAN TEKS ULASAN FILM PADA SISWA KELAS XI TKR SMK NEGERI 5 PEKANBARU SEMESTER 2 TAHUN PELAJARAN 2017-2018 - Reza Yetti (Journal on Education, 2018)
Inactive, not enthusiastic, and not taken seriously, this kind of behavior shows current phenomenon of student’s condition during Indonesian language class. One of the basic competencies that must be implemented in the classroom is the cooperation in comparing movie text review. This basic competency clearly requires the active, cooperation, and serious behavior of students. Therefore, through this research report of class action, the author tries to present a new model of Indonesian language learning that can empower the active, cooperation, and serious behavior of students during the class. This new learning model implemented in work group that able to enhance the creativity in systematically compiling report by using correct grammar. The intended learning model is the window shopping learning model. The material or learning topic is derived from the package book. This learning model is expected to influence the activeness, enthusiasm, cooperative, and serious behavior among students, that will foster a conducive and smooth learning atmosphere.